COMPARATIVE STUDY OF RIGID PAVEMENT PLANNING USING BINA MARGA 2017 AND AASHTO 1993 METHODS - Egi Firgiansyah; Prihantono Prihantono; Daryati Daryati (Jurnal Pensil : Pendidikan Teknik Sipil, 2022)
This study was conducted to determine what factors influence the differences in the results of the Bina Marga 2017 method and the AASHTO 1993 method and determine which planning results are more efficient to be applied to Letjen S. Parman Street. The research method used is a comparative method, using the existing data and the latest data from surveys. As a result of analyzing a rigid road plan with a planned age of 40 years, the Bina Marga 2017 method obtained a concrete slab with a thickness of 305 mm, and the AASHTO 1993 method obtained a concrete slab with a thickness of 280 mm. Further differences in results can be seen in the level of traffic load during the service life, the diameter of the dowels, the spacing of the tie bars, and the minimum design height of the subgrade embankment. The differences in the results of these plans are caused by two main factors, namely the factor of using the cumulative traffic growth value (R) in the Bina Marga 2017 method and the direct use of the subgrade CBR value in the AASHTO 1993 method. Based on the data that has been obtained, it is concluded that the 1993 AASHTO method provides more efficient results to be applied with considerations in terms of smaller plate dimensions and fewer connections and reinforcement requirements. Which when calculating the work cost, the AASHTO 1993 methods results give a smaller number of work volumes, so it has the possibility to provide a more economical work cost than the Bina Marga 2017 methods results.